The Tendencies of Middle School Age Students’ Leadership in Music Activity - Lasauskienė, Jolanta; Jasionienė, Gintarė (Pedagogika, 2014)
Contemporary music education particularly emphasises the objective to humanise the process of education, i.e., to focus on the individuality of the learner, to stimulation of his / her self-expression and abilities to assume the role of a leader. The article analyses the expression of leadership of basic school learners (aged 14–16) in music activity, which was explored during the research conducted in Alytus basic schools. The significant difference was established between the high level of importance of all the empirical features of manifestations of leadership (initiative, creativity, artistry, innovation) and a considerably lower level of expression of these empirical features in music activity. This substantiates the topicality of the chosen theme and possibilities of enhancing expression of leadership in basic schools. The object of the research: the tendencies of middle age school students‘ leadership in music activity. The aim of the research: to highlight the tendencies of middle age school students’ leadership in music activity. The characteristics of the sample. The research sample embraced 8–10th formers from Alytus “Šaltiniai” Basic School (n = 152) and “Dainava” Basic School (n = 86). The total number of school learners in the survey equaled 238 respondents (117 females and 121 males). The following conclusions are drawn in the article: On the basis of the insights of researchers, in this article leadership is determined as an integral individuality of personality, which is manifested in music activities through initiative, creativity, artistry and innovation of music activity (singing, music playing, creation): initiative reveals itself through fluency in singing, focused music playing, consistency of creation; creativity – individuality of singing, expressiveness of playing music, originality of creation; artistry is seen through depth of singing, focused playing, substantiation of creation; innovation – through non-standard singing, original style of playing, variety of creation. The analysis of expression of middle school age students’ leadership revealed that school learners’ leadership in music activity was most frequently expressed through innovation (originality of playing), creativity (individuality of singing), initiative (fluency in singing) and artistry (focused playing), i. e., through quality of music performance (singing and playing music). Most difficulties are encountered when school learners have to self-dependently arrange, create music, to analyse and improve own musical compositions independently and with help of a teacher. Such results have been partially predetermined by limited experience of music creative activities of senior school learners. The research revealed that the level of leadership expression of middle age school learners’ leadership in music activity is not high because of the established insufficient level of components of music arrangement (improvisation, creation of musical compositions). The significant difference was established between the importance of all the empirical features of manifestations of leadership (initiative, creativity, artistry, innovation) and the level of expression of these features in practical music activity. This demonstrates the topicality of the chosen theme and possibilities of development of expression of school learners’ leadership through music activity in general education schools.